Genetic diversity and phylogenetic relationships of the rock ptarmigan (Lagopus muta) in Japan based on mitochondrial genome analysis of museum specimens - Nobuaki Nagata; Norimasa Sugita; Kazuto Kawakami; Isao Nishiumi (PLoS ONE, 2026)
Relict species are important targets for biodiversity conservation and biogeographical research. The rock ptarmigan, Lagopus muta , which is distributed across the circumpolar region, is also found as relict populations in high mountain areas of mid-latitude regions worldwide. In Japan, isolated populations occur in the high mountain areas of Honshu Island. The Japanese L. muta japonica is threatened with extinction due to its fragmentation into multiple distribution areas, including regions where populations have already become extinct. To clarify the phylogenetic origin of the Japanese population, we conducted a mitochondrial genome-based phylogenetic analysis using museum specimens, including samples that are over 100 years old. A literature survey of the distribution areas near Japan suggested that the northern Kuril Islands represent the closest distribution area, although an alternative theory proposes that Primorsky Krai, on the eastern edge of the Eurasian continent, is nearest. Although the extracted DNA fragments were very short, we successfully determined the complete mitochondrial genome for all 18 individuals. Among the various mitochondrial regions, the control region and ND5 exhibited the greatest diversity. Network analysis of the control region from 209 individuals across all distribution areas worldwide indicated that the Japanese population is endemic, whereas no clear regional differentiation within Japan was observed in either the control region or the entire mitochondrial genome. Divergence time estimation suggests that the Japanese population diverged approximately 80,000–120,000 years ago, before the Last Glacial Maximum. This study demonstrates that useful genetic information can be recovered from degraded DNA even from specimens stored under high-temperature and high-humidity conditions in Japan, and provides a basis for re-evaluating the evolutionary history and regional genetic independence of L. muta .